Customer Behavior and Brand Promotion in Professional Sports Clubs: Developing Social Networks Marketing Model - Rasool Nazari; Elham Moshkelgosha; Mohsen Loghmani (Sports Business Journal)
Purpose: This research has been conducted to develop a social network marketing model for Sepahan Sports Club based on customer behavior and brand promotion.Methodology: The research was descriptive and conducted by a survey. The statistical population of this research includes the users and active members of the Sepahan sports club on social networks. Three hundred eighty-four people were selected by random sampling. Data collection was done using standard questionnaires, and data analysis was done using structural equation modeling using Smart PLS and SPSS software.Findings: We showed that the antecedents of social network marketing include social business drivers, brand experience, and perceived values ​​from branded web advertisements, which have a positive and significant effect on customer business relationships and brand health through customer brand engagement and brand attitude. Also, we showed that the customer's brand engagement and attitude lead to brand promotion. Making the right decision for clubs regarding social networks is very important.Originality: We showed that social networks cause the message to reach a group of contacts and improve the attitude of customers towards the club and its services, raise the level of awareness of the customers about the club and improve the mental image of, increase customer loyalty and finally the value of the customer.